2016
DOI: 10.1080/09513590.2016.1254179
|View full text |Cite
|
Sign up to set email alerts
|

In vitroeffect of myo-inositol on sperm motility in normal and oligoasthenospermia patients undergoingin vitrofertilization

Abstract: It is a known fact that abnormal seminal liquid specimens contain abnormal amounts of oxygen free radicals and reactive oxygen species (ROS), and that the use of antioxidant molecules both in vivo and in vitro leads to improvement of semen quality in terms of motility, reduction in DNA damage, with obvious consequences on the fertilization potential. Myo-inositol has been observed to have anti-oxidant properties and be present in much greater concentrations specifically in seminal liquid than in the blood. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…In male reproductive organs, myo-inositol has a central physiologic role; indeed, it is mainly produced by Sertoli cells in response to follicle-stimulating hormone (FSH) and is involved in processes including the regulation of motility, capacitation and acrosome reaction of sperm cell [ 28 , 29 , 32 ]. Moreover, its concentrations increase from the epididymis to the deferent duct; in fact, myo-inositol would seem to play an important role in the success of spermatogenesis and spermio-histogenesis as well as in osmoregulation of seminal vesicular fluid, contributing to reduce the viscosity [ 33 ] and the presence of amorphous material [ 34 ] in seminal fluid. Moreover, myo-inositol is involved in the control of intracellular Ca 2+ concentration, gene expression, cytoskeleton assembly, inhibition of mechanisms that mediate cell death by apoptosis and in maintaining the mitochondrial membrane potential (MMP) [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In male reproductive organs, myo-inositol has a central physiologic role; indeed, it is mainly produced by Sertoli cells in response to follicle-stimulating hormone (FSH) and is involved in processes including the regulation of motility, capacitation and acrosome reaction of sperm cell [ 28 , 29 , 32 ]. Moreover, its concentrations increase from the epididymis to the deferent duct; in fact, myo-inositol would seem to play an important role in the success of spermatogenesis and spermio-histogenesis as well as in osmoregulation of seminal vesicular fluid, contributing to reduce the viscosity [ 33 ] and the presence of amorphous material [ 34 ] in seminal fluid. Moreover, myo-inositol is involved in the control of intracellular Ca 2+ concentration, gene expression, cytoskeleton assembly, inhibition of mechanisms that mediate cell death by apoptosis and in maintaining the mitochondrial membrane potential (MMP) [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, several functional tests were developed, like SCD analysis or the evaluation of Mitochondrial Membrane Potential, complex methods determining unavoidably an increase in processing costs. In this context, AT is proposed as a linking bridge between different analytics dimensions, being a functional test, easy to use, with a weak economic burden, that allows a qualitative evaluation of sperm samples analysing myo‐inositol level of spermatic fluids, a fundamental molecule for spermatozoa motility (Artini et al, ; Calogero, Gullo, Vignera, Condorelli, & Vaiarelli, ; Colone et al, ; Condorelli, Vignera, Bellanca, Vicari, & Calogero, ; Condorelli et al, , ). Thanks to AT, it is possible to distinguish three spermatic classes evaluating the modifications of linear progressive motility, a useful parameter to understand the real fertilising capacity of spermatozoa (Scarselli et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have also reported the capacity of MI to induce a meaningful increase of sperm motility in oligoasthenoteratozoospermic samples after an incubation with this molecule. Regarding the importance of MI for the male fertility, finally, in the context of in vitro fertilisation (IVF), several data demonstrating the improving of in vitro sperm motility and of the fertilisation rate in ICSI after incubation with MI were also collected (Artini et al, ; Gulino et al, ). MI is involved in several processes inside the male reproductive tract as capacitation, acrosomal reaction, regulation of sperm motility, restoration of mitochondrial crests, increase in mitochondrial membrane potential (MMP) and migration of spermatozoa (Chauvin & Griswold, ; Robinson & Fritz, ).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of myoinositol, probably increasing cytosolic Ca++, and consequently, the inner mitochondrial Ca++, seems to act specifically on mitochondrial function, because others bio-functional sperm parameters did not show any significant variation. Other in vitro [72][73][74] and in vivo [75][76][77][78] studies have shown that myoinositol, alone or in combination, increased sperm motility, but the study published by Condorelli et al in 2012 is the only one that had simultaneously evaluated sperm motility and MMP.…”
Section: Effects Of Prokinetic/antioxidant Therapy On Sperm Mitochondmentioning
confidence: 99%